Case Report: Novel CSF1R Variant in a Patient With Behavioral Variant Frontotemporal Dementia Syndrome With Prodromal Repetitive Scratching Behavior - Friedberg, Adit; Ramos, Eliana Marisa; Yang, Zhongan; Bonham, Luke W.; Yokoyama, Jennifer S.; Ljubenkov, Peter A.; Younes, Kyan; Geschwind, Daniel H.; Miller, Bruce L. (Frontiers in Neurology, 2022)
CSF1R-related leukoencephalopathy is an autosomal dominant neurodegenerative disease caused by mutations in the tyrosine kinase domain of the colony stimulating factor 1 receptor (CSF1R). Several studies have found that hematogenic stem cell transplantation is an effective disease modifying therapy however the literature regarding prodromal and early symptoms CSF1R-related leukoencephalopathy is limited. We describe a 63-year-old patient with 4 years of repetitive scratching and skin picking behavior followed by 10 years of progressive behavioral, cognitive, and motor decline in a pattern suggesting behavioral variant of frontotemporal dementia. Brain MRI demonstrated prominent frontal and parietal atrophy accompanied by underlying bilateral patchy white matter hyperintensities sparing the U fibers and cavum septum pellucidum. Whole-exome sequencing revealed a novel, predicted deleterious missense variant in a highly conserved amino acid in the tyrosine kinase domain of CSF1R (p.Gly872Arg). Given this evidence and the characteristic clinical and radiological findings this novel variant was classified as likely pathogenic according to the American College of Medical Genetics standard guidelines. Detailed description of the prodromal scratching and skin picking behavior and possible underlying mechanisms in this case furthers knowledge about early manifestations of CSF1R-related leukoencephalopathy with the hope that early detection and timely administration of disease modifying therapies becomes possible.